Nanoengineered Organic Electrodes for Highly Durable and Ultrafast Cycling of Organic Sodium‐Ion Batteries. Issue 41 (22nd September 2020) - Thangavel, Ranjith; Moorthy, Megala; Ganesan, Bala Krishnan; Lee, Wontae; Yoon, Won‐Sub; Lee, Yun‐Sung
Abstract: Sodium‐ion batteries (SIBs) have become increasingly important as next‐generation energy storage systems for application in large‐scale energy storage. It is very crucial to develop an eco‐friendly and green SIB technique with superior performance for sustainable future use. Replacing the conventional inorganic electrode materials with green and safe organic electrodes will be a promising approach. However, the poor electrochemical kinetics, unstable electrode–electrolyte interface, high solubility of the electrodes in the electrolyte, and large amount of conductive carbon present great challenges for organic SIBs. In this study, the issues of organic electrodes are addressed through atomic‐level manipulation of these organic molecules using a series of ultrathin (Å‐level) metal oxide coatings (Al2 O3, ZnO, and TiO2 ). Uniform and precise coatings on the perylene‐3, 4, 9, 10‐tetracarboxylicacid dianhydride by gas‐phase atomic layer deposition technique shows a stable interphase, enhanced electrochemical kinetics (71C, 10 A g −1 ), and excellent stability (89%–500 cycles) compared to conventional organic electrode (70%–200 cycles). Further studies reveal that the chemical stability of the metal oxide coating layer plays a critical role in influencing the redox behavior, and improving kinetics of organic electrodes. This study opens a new avenue for developing high‐energy organic SIBs with performance equivalent to inorganic counterparts. Abstract : A series of uniform and ultrathin (Å‐level) metal oxide coatings employing atomic layer deposition are used to stabilize the electrode–electrolyte interface, and to reduce solubility of the organic electrode (perylene‐3, 4, 9, 10‐tetracarboxylicacid dianhydride) in organic sodium‐ion batteries. The chemical stability of the metal oxide coating layer plays a critical role in influencing the redox behavior, and improving kinetics of organic electrodes.